Factors Influencing the Company Value - Wijaya, Febryanto Yudha; Miftah, Munasiron (Garuda Prestasi Nusantara Consulting, 2024)
This research is quantitative research which aims to determine the effect of profitability, solvency, firm size, and independent commissioner on firm value. Companies included in the LQ 45 stock index that are listed on the Indonesia Stock Exchange for the 2018–2022 timeframe make up the study's population. The purposive sampling strategy was utilized to gather 125 samples for this study. In this analysis, multiple linear regression was utilized. The findings reveal that profitability has a notable and positive impact on firm value. Conversely, solvency doesn't exhibit a significant effect on firm value. Furthermore, firm size shows a significant negative correlation with firm value, while the presence of independent commissioners doesn't demonstrate a significant influence on firm value. Keywords : Profitability, Solvency, Firm Size, Independent Commissioner, Firm Value